Pedagogical challenges in times of SARS-COV-2 in early childhood education - Mesquita, Cristina (2021)
As a strategy to contain the new coronavirus transmission, educational institutions in more than 100 countries were closed since March 2020. Facing lockdown, schools sought to reorganize their operation, preparing remote activities, using platforms and other means of communication considering the need to ensure, as much as possible, the learning of children and young people. The study described in this paper resulted from the need to understand the mechanisms created by institutional leaders and childhood educators, among others, to cope with this unexpected situation. This research also aims to understand the feelings, constraints and opportunities experienced by Portuguese educators, as well as the strategies and actions developed in order to be able to provide support to children and their families. This study also documents the impact that this particular situation had on the creation of online educational offer, on the answers found by the official entities, as well as on the practices and conceptions of educators. This is a research conducted with childhood educators during the first semester of 2020, a period in which educational institutions came across the guidelines to "close the doors" and the need to continue promoting children's educational activities. Methodologically, the study assumes a qualitative approach, in order to assess the feelings, experiences and perceptions of the actors who experienced the situation. For data collection, two Focus Groups were developed, involving 20 educators and guided by a pre-structured script that comprised seven blocks of questions. The Focus Groups were recorded and, subsequently, transcribed and submitted to content analysis, whose heuristic function increases the propensity of the discovery of the reality experienced by the actors. From the content analysis, categories emerged that allowed the analysis of the discourses. The text produced was analysed and described in an articulated way, trying to apprehend the specific conditions in which it was conceived, revealing a certain order of reality, from which the narrative was made. Data analysis reveals that the majority of the pedagogical coordination of the institutions provided recommendations for remote work. Some educators indicated that they had recommendations for work from home in non-face-to-face contact, but others, through the pedagogical coordination, suggested the platforms they should use, the type of work they should do and how often they should contact children. The data highlight the efforts of some professionals to maintain contact with children. The educators are aware of the effort that families and children made during this period and reveal that this situation was more difficult for children in vulnerable situations.